2024
DOI: 10.1039/d3fb00247k
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking a nutritional treasure: health benefits and sustainable applications of spent coconut meal

Heeba Shakeela,
Kavya Mohan,
Nisha P

Abstract: This paper investigates the previously overlooked potential of spent coconut meal, a byproduct resulting from the extraction of virgin coconut oil with residual oil content 25 - 54%. Traditionally considered...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…17,21,22 In addition, the quest for producing high quality products through green and sustainable technology is a key to moving towards sustainability. 23 Although oil yield is a challenge in AEE, Prommaban et al 24 extracted pumpkin seed oil using AEE and showed that the oil performed well in antioxidant activities and anti-aging activities and could be applied in cosmetics. Besides that, during the processing and storage of oil, lipid oxidation can adversely affect sensory taste and the content of nutritional compounds and ultimately lead to quality deterioration, and thus, the oxidative stability of oil is an important index to reect oil quality.…”
Section: Introductionmentioning
confidence: 99%
“…17,21,22 In addition, the quest for producing high quality products through green and sustainable technology is a key to moving towards sustainability. 23 Although oil yield is a challenge in AEE, Prommaban et al 24 extracted pumpkin seed oil using AEE and showed that the oil performed well in antioxidant activities and anti-aging activities and could be applied in cosmetics. Besides that, during the processing and storage of oil, lipid oxidation can adversely affect sensory taste and the content of nutritional compounds and ultimately lead to quality deterioration, and thus, the oxidative stability of oil is an important index to reect oil quality.…”
Section: Introductionmentioning
confidence: 99%